ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEMISKINAN ABSOLUT MASYARAKAT PESISIR ( NELAYAN ) DI DESA SEILALE KECAMATAN NUSANIWE - Marissa Silooy (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2017)
Absolute poverty is a problem in the economy is complex multimensional. Therefore necessary to find a solution to overcome or at least reduce the level of poverty. Analysis was conducted to determine the factors that affect the level of absolute poverty in rural coastal communities seilale districts nusaniwe. Analisis data used is quantitave data dan qualitative data. Improvement of food security is a top priority board clothing, food and clothing because the board is a basic need that is most important for this human. research determined purposive with consideration that the village Nusaniwe seilale districts in the city of Ambon has poor households.